Emergence and History of Artificial Intelligence - Evelina Christova (Проблеми на постмодерността)
Artificial intelligence has entered the practice of public relations professionals and is on its way to fundamentally changing the way the PR industry works. Many professionals are already using AI applications in their work, and a large part of the public remains unaware of this fact. Very often, both parties are unaware of the history and emergence of artificial intelligence, the understanding of which is the basis for understanding its capabilities and the risks of its use. This article attempts to gather basic information on the emergence of AI and its development by the summer of 2024.Artificial intelligence